81.9k views
0 votes
Given f(x)=2x^2-3 and g(x) = x+4 What is (fg)(x)?

User Gatonito
by
5.4k points

2 Answers

2 votes

Answer:
f(g(x))=2x^2+16x+29

Explanation:


f(x)=2x^2-3\\g(x)=x+4

f of g of x means "function f, replace x by the value of g of x"


f(g(x))=2x^2-3\\f(g(x))=2(x+4)^2-3\\f(g(x))=2(x^2+8x+16)-3\\f(g(x))=2x^2+16x+32-3\\f(g(x))=2x^2+16x+29

User MontyThreeCard
by
4.9k points
3 votes

Answer:

2x^3+8x^2−3x−12

Explanation:

Given f(x)=2x^2−3 and g(x)=x+4.

What is (fg)(x)?

2x^3+8x^2−3x−12

User Sungyong
by
4.5k points